2022
DOI: 10.3390/microorganisms10102000
|View full text |Cite
|
Sign up to set email alerts
|

Partial Replacement of Oat Hay with Whole-Plant Hydroponic Barley Seedlings Modulates Ruminal Microbiota and Affects Growth Performance of Holstein Heifers

Abstract: The dairy industry is facing challenges in balancing forage supply and crop production. Therefore, forage supply based on a farm land-saving approach should be developed to overcome the human–livestock competition on farmland. The objective of this study was to learn the potential impact of partially replacing oat hay with whole-plant hydroponic barley seedlings (HBS) produced via a land-saving hydroponic method on growth performance, digestibility, and rumen microbiota in Holstein dairy heifers. In total, 39 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The experiment utilized a fully controllable environmental cultivation system (Figure 1), which was designed according to previous research on hydroponic fodder barley production [22]. Briefly, during the cultivation period, the LED lighting maintained a light quality ratio of red to blue light (R/B) at 4:1.…”
Section: The Design Of the Controllable Environmental Cultivation Sys...mentioning
confidence: 99%
“…The experiment utilized a fully controllable environmental cultivation system (Figure 1), which was designed according to previous research on hydroponic fodder barley production [22]. Briefly, during the cultivation period, the LED lighting maintained a light quality ratio of red to blue light (R/B) at 4:1.…”
Section: The Design Of the Controllable Environmental Cultivation Sys...mentioning
confidence: 99%
“…Alan et al [9] reported that milk quality improved with high fat and mineral elements by feeding hydroponic forage to dairy cows. Ren et al [10] found that hydroponic barley seedlings replaced 25% of oats and had no significant effect on the feed intake and digestibility of Holstein cows. The study of Brake et al [11] showed that wheat seedlings are rich in protein, amino acids and vitamins.…”
Section: Introductionmentioning
confidence: 99%